Associations of muscle mass, strength, and quality with all-cause mortality in China: a population-based cohort study - Wu, M; Wei, Y; Lv, J; Guo, Y; Pei, P; Li, J; Du, H; Yang, L; Chen, Y; Sun, X; Zhang, H; Chen, J; et al. (Wolters Kluwer, 2022)
Background It remains unclear about the association of muscle mass, strength, and quality with death in the general Chinese population of diverse economical and geographical backgrounds. The present study aimed to comprehensively examine such associations across different regions in China.